Ventricular tachycardia ablation in patients with structural heart disease: single centre experience - KEPEZ, ALPER (MARMARA UNIV, FAC MEDICINE, 2020)
Objective: The aim of this study is to report our institutional experience with ventricular tachycardia (VT) ablation in patients with structural heart disease. Patients and Methods: A total of 36 consecutive patients (31 male, age: 62.8 +/- 13.2 years) who had undergone VT ablation in our institution between 01.01.2017 and 01.05.2019 were included in the analysis. Results: A total of 27 patients with the diagnosis of ischemic cardiomyopathy and 9 patients with the diagnosis of nonischemic cardiomyopathy had undergone VT ablation. VT ablation was successful in 32 (88.9%) patients. There were no major procedural complications; however, one patient with ischemic cardiomyopathy died 48 hours after the procedure because of post-ablation cardiogenic shock. Another patient with unsuccessful V'I' ablation died during hospitalization due to electrical storm. Endocardial ablation was performed in 23 (63.9%) patients and epicardial or combined endocardial and epicardial ablation was performed in 13 (36.1%) patients. Substrate ablation was the dominant strategy in 29 (80.6%) patients whereas activation snapping and isthmus ablation was performed in 7 (19.4%) patients. Conclusion: Our experience confirms the effectiveness and safety of VT ablation in patients with structural heart disease who are resistant to medical therapy and/or who receive recurrent implantable cardioverter-defibrillator shocks.
Keywords: Ventricular tachycardia; Radiofrequency ablation; Cardiomyopathies; CATHETER ABLATION